1498. Sexually Transmitted Infections Among Persons Living with HIV Infection and Receiving Care in the District of Columbia: Time with Viral Load Above 1, 500 as Proxy for Risk of Transmission. (26th November 2018) - Secco, Alessandra; Akselrod, Hana; Lucar, Jose; Rayeed, Nabil; Leighton, Nicolas; Parenti, David; Benator, Debra
Abstract: Background: The District of Columbia (DC) has one of the highest HIV infection rates among metropolitan areas in the United States, as well as recent increases in the incidence of sexually transmitted infections (STI), particularly among men who have sex with men (MSM). A previous study of the DCCohort, (a longitudinal observational cohort of HIV-infected persons receiving care in DC, identified a disconcertingly high incidence of detectable HIV viral load (VL) close to the time of STI occurrence. Studies have identified time spent with HIV VL above 1, 500 copies/mL as a proxy measure for risk of sexual transmission of HIV. The present study examines percentage of time with VL above 1, 500 among persons living with HIV infection (PLWH) with incident STI. Methods: We conducted a retrospective cohort analysis measuring STI incidence (including syphilis, gonorrhea, chlamydia) among all individuals enrolled in the DC Cohort from 2011 to 2015. We conducted descriptive analysis to estimate the number of days with HIV VL >1, 500 copies/mL, relative to the total number of days of observation, among those with an incident STI during the same observation period. Results: We analyzed data for 5, 033 DC Cohort enrollees for whom STI data and at least two VL observations were available. During a median observation of 32.8 months, 4, 610 individuals had no STI and 423 (8%) individuals had any incident STI; 293 had one and 130 had two or more. Of the 423 participants with an incident STI, 67.8% did not spend any time with a VL >1, 500; 10.7% had VL >1, 500 during > 0 to < 25% of the time; 7.3% had VL >1, 500 during 25 to < 50% of the time; 5.0% had VL >1, 500 during 50 to < 75% of the time; and 9.2% of participants with any incident STI had VL >1, 500 during 75–100% of the time. Among participants with two or more STIs over the observation period, 17.7% spent greater than 50% of the time with a viral load >1, 500. Conclusion: Among PLWH with incident STIs, as many as one-third spent considerable time with a VL >1, 500 copies/mL, placing them at increased risk of transmitting HIV to others. Public health interventions need to focus on mitigating the risk of HIV transmission in the highest-risk populations, while also seeking to reduce overall incidence of other STIs. Disclosures: All authors: No reported disclosures.